The Influence of Learning Motivation, Socioeconomic Status, and Physical Fitness on PJOK Learning Outcomes - Panjaitan, Mangatur; Welis, Wilda; Bakhtiar, Syahrial; Damrah, Damrah; Zarya, Fiky (JETL (Journal of Education, Teaching and Learning), 2024)
The problem of the research is the low learning outcomes of Physical Education, Sports and Health (PJOK) at SMA Negeri 16 Batam. The low learning outcomes of students can be caused by several determinant factors, including learning motivation, socioeconomic status, and physical fitness. The purpose of the study is to analyze the influence of learning motivation, socioeconomic status, and physical fitness on the learning outcomes of physical education, sports, and student health. This type of research is using a quantitative method with a path analysis approach. The population of this study is 247 grade XII students at SMAN 16 Batam. The sample withdrawal in this study used the Total Sampling Technique as many as 247 respondents. Data is collected using instruments. PJOK learning outcomes from the second semester (even) grades of PJOK subjects, learning motivation and socioeconomic status through questionnaires, then physical fitness through the archipelago student fitness test (TKPN) which has been standardized by the Ministry of Youth and Sports in 2022 which consists of 5 tests, namely: a, Body Mass Index (BMI), b, V Sit and Reach, c, Sit Up 60 seconds, d,  Squat Thrust 30 seconds, e, Pacer Test. The results of the study showed that 1) there was a direct influence of learning motivation on PJOK learning outcomes, 2) there is a direct influence of socioeconomic status on PJOK learning outcomes, 3) there is a direct influence of physical fitness on PJOK learning outcomes, 4) there is an indirect influence between learning motivation, socioeconomic status, and physical fitness simultaneously on PJOK learning outcomes. This can be interpreted that students' PJOK learning outcomes can increase by increasing learning motivation, socioeconomic status, and maximizing students' physical fitness